If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) = 6x + -21 Reorder the terms: 3(5 + x) = 6x + -21 (5 * 3 + x * 3) = 6x + -21 (15 + 3x) = 6x + -21 Reorder the terms: 15 + 3x = -21 + 6x Solving 15 + 3x = -21 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 15 + 3x + -6x = -21 + 6x + -6x Combine like terms: 3x + -6x = -3x 15 + -3x = -21 + 6x + -6x Combine like terms: 6x + -6x = 0 15 + -3x = -21 + 0 15 + -3x = -21 Add '-15' to each side of the equation. 15 + -15 + -3x = -21 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = -21 + -15 -3x = -21 + -15 Combine like terms: -21 + -15 = -36 -3x = -36 Divide each side by '-3'. x = 12 Simplifying x = 12
| 23+82= | | 42=-2t+9t | | 7/6multiply3/5 | | 4(w+2)=8 | | 28=-4+8x | | 6x-6y/-5z | | 6=5b+1 | | (2q+4)(3q+1)= | | 16x^4+26x^2+3=0 | | 690/a | | 1=d/4 | | X+.75x=65 | | 5cos^2x-cosx+3=0 | | -36-12x=48 | | 3-(5x+7)=17-8x | | 3(x+45)=2(x+40)+(2x) | | -6-9x+1=7x | | -2y+4x=-4 | | 4x-3(4x+21)=-143 | | -6-9+1=7x | | 4(d+50)=114 | | x^7+x^5+5=0 | | 10a-2ab= | | 8/x=-9 | | 7x+9y=192 | | 50x-80=70x+30 | | 4y+6(-2)y=10 | | 2(-4x+12)=144 | | 1.5(4-w)=-(1.5-8) | | 2logx-log(x+9)-log(x-9)=0 | | 4x=(2x+10) | | y-9=-5/7x |